Consumers' Attitudes towards Edible Wild Plants: A Case Study of Noto Peninsula, Ishikawa Prefecture, Japan. (7th March 2012) - Chen, Bixia; Qiu, Zhenmian
Abstract : This study explored the rural revitalizing strategy in FAO's Globally Important Agricultural Heritage System (GIAHS) site in Noto Peninsula, Ishikawa Prefecture of Japan, using a case study of edible wild plants. This study assessed the current and possible future utilization of edible wild plants as one important NTFP by clarifying the attitudes of consumers and exploring the challenges of harvesting edible wild plants. Traditional ecological knowledge associated with edible wild plants and the related attitudes of consumers towards wild plants was documented. A questionnaire survey found that a majority of the respondents held positive attitude towards edible wild plants as being healthy, safe food, part of traditional dietary culture. Increasing demand of edible wild plants from urban residents aroused conflicts with local residents' interest given that around 86% of the forested hills are private in Noto Region. Non timber forest products (NTFP) extraction can be seen as a tool for creating socioeconomic relationships that are dependent on healthy, biodiverse ecosystems. It was suggested that Japanese Agricultural Cooperatives (JA) and Forestry Cooperatives (FCA) could be involved with GIAHS process. As important traditional dietary and ecological system, edible wild plants should be a part of GIAHS project for rural revitalization.